2014
DOI: 10.1016/j.yebeh.2014.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Current beliefs and attitudes regarding epilepsy in Mali

Abstract: Our study demonstrates widespread misconceptions in Mali regarding epilepsy. Our findings argue for more education initiatives focused on the entire population, including traditional healers, to provide knowledge, reduce stigma, and improve quality of life for individuals living with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 20 publications
4
45
1
Order By: Relevance
“…Almost all respondents (99.5%) knew that epilepsy is not an infectious disease. In comparison, a lesser proportion of Turkish parents (89.5%) were certain about this fact, while in Mali, 21% of parents did not believe that the disease is contagious [18,2]. However, considerably low percentage of parents (68.1%) in our study was certain that epilepsy was not a psychiatric disorder, which may also reflect certain cultural beliefs.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Almost all respondents (99.5%) knew that epilepsy is not an infectious disease. In comparison, a lesser proportion of Turkish parents (89.5%) were certain about this fact, while in Mali, 21% of parents did not believe that the disease is contagious [18,2]. However, considerably low percentage of parents (68.1%) in our study was certain that epilepsy was not a psychiatric disorder, which may also reflect certain cultural beliefs.…”
Section: Discussioncontrasting
confidence: 75%
“…It has been noted that traditional beliefs and lack of knowledge strongly influence attitudes towards epilepsy [1][2][3]5]. Keeping in mind that this chronic neurological disorder occurs in 0.5 to 1.0% of children under the age of 16 [7], we have found that the burden of epilepsy most commonly involves informal caregivers.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The belief that epilepsy is contagious has been repeatedly demonstrated in other African countries [3][4][5][6][7][13][14][15]. This belief greatly impacts people with epilepsy and their safety during a seizure because bodily fluids (saliva, sweat, urination) are common during a seizure, and if someone believes that they may "catch" epilepsy, they will be less likely to help a patient in need.…”
Section: Discussionmentioning
confidence: 99%